2019
DOI: 10.4314/jasem.v23i7.10
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity of Xylene on the African Catfish <i>Clarias gariepinus</i>

Abstract: Acute toxicity of xylene on an African catfish (Clarias gariepinus) was carried out. A total of 210 catfish C. gariepinus juveniles with mean length 15.20±2.3cm, and mean weight of 10.23±2.6g were obtained from the University of Port Harcourt Demonstration Farm. The test was determined for 96hour median lethal concentration using concentrations of 250ml/l, 200ml/l, 150ml/l, 100ml/l, 50ml/l, 25ml/l and 0.0ml/l (control) which gave a LC50 value of 63.965ml/l with upper and lower confidence limits at 106.53 ml/l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 9 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…New stock solution attributes while the watersoluble fraction (WSF) of the Diesel used was prepared using the standard method by Anderson et al and Orlu and Ogbalu, [12,13]. The Combination of both chemicals at a 50:50 ratio was prepared using the method described by Davies et al [7].…”
Section: Preparation Of a Working Stock Solution For Xylene And Dieselmentioning
confidence: 99%
See 4 more Smart Citations
“…New stock solution attributes while the watersoluble fraction (WSF) of the Diesel used was prepared using the standard method by Anderson et al and Orlu and Ogbalu, [12,13]. The Combination of both chemicals at a 50:50 ratio was prepared using the method described by Davies et al [7].…”
Section: Preparation Of a Working Stock Solution For Xylene And Dieselmentioning
confidence: 99%
“…This study has shown that there were noticeable behavioural changes observed at the different concentrations of the chemicals (Xylene: Diesel) which were below those concentrations that led to mortality. Toxicity of chemicals to aquatic organisms has also been reported to be affected by dissolved oxygen, size, age, water quality, and formulations of chemicals (Pandey et al, [59]) and death as reported by (Davies et al [9]).…”
Section: Responses Of C Gariepinus Exposed To the Combined Chemicalsmentioning
confidence: 99%
See 3 more Smart Citations